Ruptured Spinal Arteriovenous Malformation: A Rare Cause of Paraplegia in Pregnancy - Clare E. Thiele (Hindawi Limited, 2018)
Background. Ruptured spinal arteriovenous malformation (AVM) is a rare cause of paraplegia in pregnancy, with only a few case reports describing complications from spinal AVMs during pregnancy in the literature. Case. A 32-year-old woman presented at 37 weeks gestation with back pain and rapidly progressive lower limb neurological symptoms. MRI showed a previously undiagnosed spinal AVM at T8. A healthy girl was delivered by caesarean under general anaesthesia to facilitate further investigation. After spinal angiography, it was concluded the most likely aetiology was acute rupture of an intra- and perimedullary AVM with associated haemorrhage at T8 secondary to venous compression from the enlarged uterus at L5 causing high pressure within the AVM and subsequent rupture. The neurosurgical and interventional radiology teams felt the lesion was not amenable to surgical or endovascular intervention. The patient remained paraplegic with no sign of neurological recovery six months after delivery. Conclusion. While new onset paraplegia during pregnancy secondary to ruptured spinal AVM is very rare, it is important to discuss these cases to inform future practice. In contrast to previous case reports, our patient did not spontaneously recover after delivery and was not amenable to surgical or endovascular treatment.